Minimizing cost of empty container repositioning in port hinterlands, while taking repair operations into account. (January 2017) - Hjortnaes, T.; Wiegmans, B.; Negenborn, R.R.; Zuidwijk, R.A.; Klijnhout, R.
Abstract: Shipping companies are striving to optimize their empty container repositioning strategies which also contribute to reduced congestion and environmental improvements. In this paper we propose a multi-commodity model that makes an explicit distinction between flows of non-damaged containers, on the one hand, and flows of damaged containers, on the other. The model is tailored for the repositioning of these containers in the representative setting of a network of off-dock empty depots, ocean terminals, and inland terminals. In our case study, cost savings of up to 17% are found, depending on the composition of the network, container type, and particular evacuation and repositioning strategy. In particular, directly transporting containers from inland terminals to other inland terminals (direct repositioning) results in cost savings of up to 15% for dry containers and up to 17% for reefer containers. Furthermore, the total costs might be optimized by actually preventing the container failure from occurring possibly leading to considerable additional cost reductions. Finally, exporting damaged containers might seem to be the optimal solution from a regional cost perspective, but, this does not necessarily lead to total cost optimization from the global perspective. Highlights: A new model for both damaged and non-damaged empty container flows is proposed. The theoretical model is validated against actual data from Maersk Line. Cost savings of 17% are identified when steering empty containers.